LiPId license plate identifier : a motor vehicle license plate recognition system using ant colony systems and support vector machines - Castillo, Jephrey S.; Tanjutco, Aldwin Jayson P.; Valdez, Allan Michael C. (2005)
LIcense Plate IDentifier (LiPId) is a license plate recognition and identification system that uses Ant Colony Optimization for plate localization and Support Vector Machines for character recognition. It recognizes license plate characters from an image extracted from a video sequence captured from a standard video camera. In this paper, a system for identifying Philippine license plates is proposed. The LiPId system consists of four main phases. Each phases consists of modules, and is further divided into sub-modules as needed. The first phase produces images gathered from frames of a live video capture. This consists of two modules video processing and image processing respectively. Video processing captures video from an external source. Simultaneously, the video is processed and broken down into frames. Plate localization on the captured vehicle image follows, which outputs the localization of the plate number in a particular image using the frames from the first phase. The Plate Matrix Generation and the Plate Matrix Processing modules make up the second phase. During the transition between the first two phases, the frames will be analyzed by getting the HSV values of each pixel producing a two-dimensional matrix, which will represent the image on computer memory. The color values will be the basis of the Ant System to produce locations of candidate plates. These candidate plates will be re-processed to obtain the final location of the license plate, which will be isolated from the image. The localized plate will then enter character segmentation which will divide the plate into six sub-images. Individual characters will then be recognized using a trained Support Vector Machine which classifies each letter and number, and will eventually recognize the license plate.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Automobile license plates -- Identification; Optical character recognition devices; Pattern recognition systems; Image processing- -- Digital techniques; Ants -- Behavior -- Mathematical models; Support vector machines; LiPId (LIcense Plate IDentifier).